GAMBARAN KADAR NITROGEN PADA FESES YANG TERINFEKSI OLEH Ascaris lumbricoides - Darmadi - Adi (Akademi Kesehatan John Paul II Pekanbaru, 2022)
Nitrogen is part of the main building blocks of protein in the human body. Nitrogen is formed from the breakdown of protein by the body. In the body nitrogen is used as a raw material for the formation of amino acids. In general, the results of the body's metabolism will be excreted through the feces and some in the urine, one of which is nitrogen. With Ascaris lumbricoides infection, nitrogen metabolism will be disrupted, so that excess levels of a substance in the body will be excreted through urine and feces. Nitrogen levels in the body will be disturbed when the absorption of nutrients by the body is disturbed, one of the disturbances in nitrogen absorption is the occurrence of worm infections. The types of helminth infections that commonly occur are soil-transmitted helminths such as Ascaris lumbricoides worm infection. The purpose of this study was to determine the comparison of nitrogen levels in the feces of patients with Ascariasis infection and in normal feces. Nitrogen levels were tested by examining the nitrogen levels in the feces which contained Ascaris worm eggs in the stool specimen. The results showed that nitrogen levels in feces infected by worms included sample A nitrogen content of 0.19%, sample B obtained nitrogen content of 2.16%, and nitrogen content in sample C was 2.05% with an average of 1.46% while This nitrogen indicates that there is an increase in nitrogen levels in the body due to ascariasis infection in the body.